Tetrix: A novel Tetris-based paradigm for neuroimaging research and clinical applications - Julius Grote; Julia Elina Stocker; Jens Sommer; Anna-Maria Hamm; Henrik Kessler; Andreas Jansen (Behavior Research Methods, 2026)
Abstract Tetris is a widely used computer game, not only for entertainment purposes but increasingly in cognitive and clinical neuroscience research. Despite its frequent application in experiments, the neural mechanisms underlying gameplay remain insufficiently understood. Prior work suggests that cognitive control during complex visuospatial tasks, like Tetris, engages the attention network as well as regions supporting visuospatial working memory, mental imagery, and motor planning. However, researchers currently lack a standardized paradigm to investigate these processes. To address this gap, we introduce Tetrix, a novel and flexible Tetris-based paradigm designed for use in behavioral and functional magnetic resonance imaging (fMRI) experiments. With a broad range of customizable features, Tetrix can be adapted to specific experimental requirements or used in its default configuration. To validate the paradigm’s feasibility for neuroimaging applications, we conducted a proof-of-concept fMRI study with six participants. Results revealed robust bilateral activity in the frontal eye fields and posterior parietal cortex – key nodes of the dorsal attention network. Additional activation was found in the cerebellum and occipital cortex. These regions are thought to support rapid spatial orienting, the encoding and maintenance of visuospatial working memory, and motor planning. The observed activation patterns therefore align with theoretical expectations and confirm Tetrix’s utility for probing relevant cognitive functions in fMRI. Moreover, the pilot dataset and corresponding effect size maps provide a valuable resource for estimating statistical power in future research. In summary, this article introduces Tetrix as a standardized and validated paradigm for functional neuroimaging and beyond. It is available at: https://github.com/JuliusGrote/Tetrix_Psychopy .